EFFECT OF THE INCLUSION OF BARLEY GRAIN AND SUNFLOWER SEED IN A FORAGE DIET ON THE OPTIMUM CULLING AGE OF GUINEA PIGS - Lozada P., Patricia (2013)
The study evaluated the effect of the energy supplementation on the optimal culling age of guinea pigs (Cavia porcellus) in the Peruvian highlands. Two hundred guinea pigs of 4 weeks old were distributed in fours treatments during 13 weeks: forage ad libitum (T0), forage ad libitum plus 10 g barley grain/animal (T1), forage ad libitum plus 7 g sunflower seed/animal (T2), and forage ad libitum plus 5 g barley grain and 3.5 g sunflower seed/animal (T3). A randomized complete block design, with initial live weight defining the block, and 5 experimental units of 10 animals each, was applied. The energy supplementation improved body weight gain and feed conversion index (p<0.05), whereas the combination of sunflower seed and barley grain had an additional effect on body weight gain (T3) and the inclusion of sunflower (T2) on feed conversion index (p<0.05). The energy supplementation had no effect on production cost, benefit/cost ratio or optimal culling age.